ANALISIS HUBUNGAN BEBERAPA FAKTOR DENGAN PEMANFAATAN PELAYANAN KUNJUNGAN KE-4 (K4) PADA IBU HAMIL TAHUN 2019 (STUDI KASUS DI WILAYAH KERJA PUSKESMAS KALIMAS, KECAMATAN RANDUDONGKAL, KABUPATEN PEMALANG) - Novitasari, Bayu Putri; Nugroho, Raden Djoko; Winarni, Sri; Mawarni, Atik (Jurnal Kesehatan Masyarakat (e-Journal), 2020)
In 2018 Kalimas Health Center had the hughest K4 achievement anda had met the Minimum Service Standards (100.71%). In the implementation of K4 there are differences in the standard K4 coverage, K4 access and K4 target. This can be seen from the May 2019 standard K4 coverage of 31.24% K4 coverage of access is 35.59% and the target of 41.67%. This study aims to analyze the relationship of several factors with the use of K4 services in the work area of Kalimas Health Center in 2019. This type of research is an explanatory research with cross sectional study design. The study population numbered 112 pregnant women. By using simple sampling random technique, 93 sample were selected. Statistical test included: univriate and bivariate (Chi Square; Continuity Correction). Research result show 75.3% of mothers have low parity, 71.0% of mothers have high family income (?UMK), 71.0% of mothers have ease in accessing accessibility, 81.7% of mothers have high decision making authority, 73.1% have support from cadres, 64.5% the availability of pregnancy information, 53.8% of mothers get incomplete services, 82.8% of mothers have never had a miscarriage, and 82.8% of mothers use K4 services with access. There is no relationship of parity, family income, accessibility, women?s authority in decision making, health cadres support, history of miscarriage with the use of K4 services. There is relationship between the availability of pregnancy information (p-value = 0.006), completeness of service (p-value = 0.032) with the use of K4 services. Optimizing the provision of information through consoling to mothers, providing IEC (Communication, Information anda Education), conducting interpersonal communication, anda making regular visits to mother with help of midewives.